Peran Majelis Solawat dalam Mencegah Degradasi Moral Remaja di Desa Bekiring - Sugiyono Sugiyono; Hanafi Hadi Susanto (Institut Agama Islam Sunan Giri Ponorogo, 2023)
The solawat assembly is a religious assembly in which there are groups of people who chant solawat to seek intercession from Allah SWT. and the Prophet Muhammad SAW. Assemblies are a source of religious teachings that teach noble morals, provide guidance in life, help with mental difficulties and overcome moral problems. Moral problems are a problem that is becoming a ghost for today's society, because with technological advances and the era of existing morality starting to decline and even being ignored. Moral damage can interfere with shared comfort. The Zahrotul qolbi prayer assembly at Dsa Bekiring will have a tremendous impact on the moral degradation of youth. With this solawat assembly, youth in Bekiring Village will be filled with positive and religious activities that help reduce the moral degradation of youth. The method used in this study is a qualitative descriptive method which is a study that describes natural phenomena that occur in the Bekiring Village Community environment, the approach used is a social and psychological approach. Collecting data using observation, interviews, and documentation. The resource persons were taken from members of the solawat assembly who are still active and the community. The results of this research are the role of the solawat assembly in building youth morality through religious activities including reciting solawat, routine recitation, spiritual cleansing and commemorating Islamic holidays.